(untitled) (Research, Society and Development, 2022)
Objective: To analyze the impact of bariatric surgery on the 10-year Framingham BMI cardiovascular risk score, comparing pre- and postoperative data from those patients undergoing sleeve gastrectomy and Roux-en-Y gastroplasty. Methodology: Retrospective, observational, single-center study, performed by collecting data from 50 participants undergoing laparoscopic bariatric surgery, in a private institution, between 2019 and 2021. After exclusion criteria, 40 patients were studied. Those who met the criteria for calculating the Framingham risk score (FCR) BMI at 10 years, with analysis after 6 and 12 months, were included. Data examined by percentage frequency, Shapiro-Wilks, Mann-Whitney and Kruskal-Wallis tests. Admitted significance level was 5%. Results: The FHR reduction rate was 3.41% in females and 7.38% in males. The variation of the normality pattern of the FHR for age in the pre-surgical period was 4.9%, after 6 months and 1 year it was reduced to 1.5% and 0.7%, respectively. There was no statistical difference between the procedures. Specific treatment for comorbidities was discontinued in 80% of those with diabetes and 85.7% of those with hypertension. Conclusion: There was a significant association between bariatric surgery and reduction in FHR, regardless of the technique used.